Інформаційна система визначення ступеня пошкодження конструкційних матеріалів - Сироїд, Віктор Ігорович; Syroid, Viktor Ihorovych (Національний університет "Львівська політехніка", 2025)
У сучасній промисловості кожна несправність – це втрата часу, ресурсів і фінансових можливостей. У більшості випадків, причиною таких несправностей є старіння або пошкодження обладнання чи елементів конструкцій. Від їх технічного стану, залежить безперебійна робота виробництва, його економічна ефективність та безпека персоналу [1]. Будь-яка тріщина, розшарування чи деформація конструкційного елемента може стати причиною аварії або дороговартісного простою. Тому контроль стану і своєчасне виявлення пошкоджень матеріалів є одним із найважливіших завдань сьогодення. Традиційні методи діагностики часто потребують зупинки роботи обладнання, що не завжди можливе у виробничих умовах. Натомість, метод акустичної емісії дозволяє “прослухати” матеріал під час роботи та визначити, коли в його структурі починають виникати зміни [2]. Однак ефективність даного методу значною мірою залежить від того, наскільки точно та швидко вдається проаналізувати отримані дані. У промислових умовах обсяг інформації може бути настільки великим, що самостійний аналіз або частково автоматизована обробка стає малоефективною. Саме тому виникає потреба у розробленні інформаційних систем [3], що здатні аналізувати дані та визначати ступінь пошкодження конструкційних матеріалів та обладнання. Сьогодні такі рішення особливо актуальні, а найкращих результатів досягають завдяки інтеграції нейронних мереж у такі системи. Вони здатні відокремлювати корисну інформацію від шумів і розпізнавати закономірності, які важко помітити людині [4]. Завдяки цьому нейронні мережі можуть швидко й точно визначати ступінь пошкодження. Об’єктом дослідження цієї магістерської кваліфікаційної роботи є процес визначення ступеня пошкодження конструкційних матеріалів. Предметом дослідження виступають методи, алгоритми та програмні засоби, що дозволяють обробляти й класифікувати дані акустичної емісії з використанням нейронних мереж для виявлення та визначення ступеня пошкодження матеріалу. Метою даної роботи є розроблення інформаційної системи, яка дозволяє визначати ступінь пошкодження конструкційних матеріалів. Розроблена система має поєднувати етапи обробки даних, навчання нейронних мереж та визначення ступеня пошкоджень. Для досягнення поставленої мети потрібно виконати такі завдання: • Проаналізувати сучасні наукові підходи та існуючі рішення; • Обґрунтувати використання нейронних мереж для аналізу даних акустичної емісії даних і визначення ступеня пошкодження; • Провести системний аналіз предметної області, сформувати вимоги до інформаційної системи та розробити її концептуальну модель; • Створити структуру й архітектуру системи, визначивши послідовність основних етапів; • Дослідити різні типи нейронних мереж і вибрати оптимальну модель для задачі класифікації пошкоджень; • Виконати практичну реалізацію інформаційної системи. Отож, у результаті виконання магістерської кваліфікаційної роботи розглянуто доцільність застосування нейронних мереж, для визначення ступеня пошкодження конструкційних матеріалів. Проведено системний аналіз предметної області, визначено мету та завдання дослідження, сформовано структуру майбутньої системи. Побудовано дерево цілей і розроблено UML-діаграми, що описують логіку роботи системи. Розглянуто архітектури нейронних мереж та обґрунтовано вибір для впровадження у систему. Завдяки цьому виконано практичну реалізацію інформаційної системи, яка інтегрує нейронні мережі для автоматичного визначення ступеня пошкодження конструкційних матеріалів.

In modern industry, each malfunction is a loss of time, resources and financial opportunities. In most cases, the cause of such malfunctions is aging or damage to equipment or structural elements. The uninterrupted operation of production, its economic efficiency and personnel safety depend on their technical condition [1]. Any crack, delamination or deformation of a structural element can cause an accident or costly downtime. Therefore, condition monitoring and timely detection of material damage is one of the most important tasks today. Traditional diagnostic methods often require stopping the equipment, which is not always possible in production conditions. In contrast, the acoustic emission method allows you to “listen” to the material during operation and determine when changes begin to occur in its structure [2]. However, the effectiveness of this method largely depends on how accurately and quickly the obtained data can be analyzed. In industrial conditions, the volume of information can be so large that independent analysis or partially automated processing becomes ineffective. That is why there is a need to develop information systems [3] that are able to analyze data and determine the degree of damage to structural materials and equipment. Today, such solutions are especially relevant, and the best results are achieved through the integration of neural networks into such systems. They are able to separate useful information from noise and recognize patterns that are difficult for a person to notice [4]. Thanks to this, neural networks can quickly and accurately determine the degree of damage. The object of research of this master’s qualification work is the process of determining the degree of damage to structural materials. The subject of research is methods, algorithms and software that allow processing and classifying acoustic emission data using neural networks to detect and determine the degree of material damage. The purpose of this work is to develop an information system that allows determining the degree of damage to structural materials. The developed system should combine the stages of data processing, training of neural networks and determination of the degree of damage. To achieve the set goal, the following tasks must be performed: • Analyze modern scientific approaches and existing solutions; • Justify the use of neural networks for analyzing acoustic emission data and determining the degree of damage; • Conduct a system analysis of the subject area, formulate requirements for the information system and develop its conceptual model; • Create the structure and architecture of the system, determining the sequence of the main stages; • Investigate different types of neural networks and select the optimal model for the damage classification task; • Perform practical implementation of the information system. So, as a result of the master’s qualification work, the feasibility of using neural networks to determine the degree of damage to structural materials was considered. A system analysis of the subject area was conducted, the goal and objectives of the study were determined, the structure of the future system was formed. A goal tree was built and UML diagrams were developed that describe the logic of the system. Neural network architectures are considered and the choice for implementation in the system is justified. Thanks to this, a practical implementation of an information system that integrates neural networks for automatic determination of the degree of damage of structural materials is carried out.
Information System for Determining the Degree of Damage to Structural Materials
Keywords: 8.126.00.01; інформаційна система; визначення ступеня пошкодження; штучні нейронні мережі; аналіз даних; точність. Перелік використаних джерел: 1. Application of object detection algorithms in non-destructive testing of pressure equipment: a review / W. Wang et al. Sensors. 2024. Vol. 24; no. 18. P. 5944. URL: https://doi.org/10.3390/s24185944 (date of access: 30.10.2025). 2. Short review of the use of acoustic emissions for detection and monitoring of cracks / A. Carrasco et al. Acoustics australia. 2021. Vol. 49; no. 2. P. 273–280. URL: https://doi.org/10.1007/s40857-021-00219-4 (date of access: 30.10.2025). 3. Zemmouchi-Ghomari L. Basic concepts of information systems. Contemporary issues in information systems - a global perspective [working title]. 2021. URL: https://doi.org/10.5772/intechopen.97644 (date of access: 30.10.2025). 4. An improved mask R-CNN micro-crack detection model for the surface of metal structural parts / F. Yang et al. Sensors. 2023. Vol. 24; no. 1. P. 62. URL: https://doi.org/10.3390/s24010062 (date of access: 30.10.2025); information system; determination of the degree of damage; artificial neural networks; data analysis; accuracy. List of used sources: 1. Application of object detection algorithms in non-destructive testing of pressure equipment: a review / W. Wang et al. Sensors. 2024. Vol. 24; no. 18. P. 5944. URL: https://doi.org/10.3390/s24185944 (date of access: 30.10.2025). 2. Short review of the use of acoustic emissions for detection and monitoring of cracks / A. Carrasco et al. Acoustics australia. 2021. Vol. 49; no. 2. P. 273–280. URL: https://doi.org/10.1007/s40857-021-00219-4 (date of access: 30.10.2025). 3. Zemmouchi-Ghomari L. Basic concepts of information systems. Contemporary issues in information systems - a global perspective [working title]. 2021. URL: https://doi.org/10.5772/intechopen.97644 (date of access: 30.10.2025). 4. An improved mask R-CNN micro-crack detection model for the surface of metal structural parts / F. Yang et al. Sensors. 2023. Vol. 24; no. 1. P. 62. URL: https://doi.org/10.3390/s24010062 (date of access: 30.10.2025)